Peningkatan Keterampilan Bisnis Gen-Z melalui Pelatihan Pembuatan Deodorant Spray Berbahan Alami - Nada Hikmatul Ilmi; Nur Istiqamah; Baidina Zahra; Nabilla Salsa Bila; Agus Seiry; Nadia Khairunnisa; Muhammad Wafa; Zulkifli (Politeknik Piksi Ganesha Indonesia, 2025)
Generation Z has a significant influence in various aspects of life, such as business, education, and popular culture. When Gen Z was born, the use of technology such as the internet, smartphones, and social media was becoming popular, so Gen Z has a very close relationship with technology usage. Therefore, Gen Z has the opportunity to be encouraged to creatively generate business ideas. The purpose of this service is to provide business ideas through training in the production of natural ingredient deodorant spray made from alum, which is available in the village of Terantang. This service article uses the ABCD method (asset-based community development) with data obtained from observations and interviews. The result of this service is the creation of business skills for Gen Z at SMPN 5 Sampit from natural resources, namely tawas stone, which was previously only used as a water purifier, into a new business idea product.